PENGARUH CORPORATE GOVERNANCE DAN POLITICAL CONNECTION TERHADAP TAX AVOIDANCE DAN DAMPAKNYA PADA NILAI PERUSAHAAN - Suwandi Ng; Felicia Katrin Phie (SIMAK, 2020)
This study aims to investigate the influence of corporate governance and political connection to tax avidance, and its impact on value of firm. The population used is all companies listed on the Indonesia Stock Exchange (IDX) with the study period 2015-2017. The sample size is 102 companies per year, selected by purposive sampling method. This study uses documentary data, namely annual reports and financial reports. Path analysis was used to analyze data and hypothesis test of mediation was done by sobel test. The results of this study indicate that corporate governance has a negative and significant influence on tax avoidance, while the political connection has a positive and significant effect on tax avoidance. Tax avoidance has a negative and significant influence on firm value. In addition, tax avoidance can mediate the influence of political connection on firm value. The implications of this research are companies with high levels of corporate governance practices that have better controls, thus reducing tax avoidance. While the relationship of political connection encourage companies to act more aggressively in tax avoidance action. Tax avoidance conducted by the company shows the practice of tax avoidanceso as to lower the level of investor confidence in investing its capital that impact on the decline in corporate value.